Didactics as a scientific and pedagogical discipline (2019)
The teaching and learning of natural sciences constitute a development process and maturation in students’ thinking, aiming to promote concrete discussions that provide theoretical and practical elements in which      is possible to demonstrate necessary and fundamental relationships between conceptual, social and cultural aspects of the natural sciences. The present document shows some conceptual references around didactics as a science of education and some key aspects about the process of accompaniment of students of the Bachelor in Basic Education with emphasis in Mathematics, Humanities and Spanish Language, in the area of natural sciences, taking into account the curricular guidelines of the area, the disposition of the Ministerio de Educación Nacional de Colombia and its relationship with teaching didactic models.